2020
DOI: 10.1101/2020.06.18.158196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bcr-Abl tyrosine kinase inhibitor imatinib as a potential drug for COVID-19

Abstract: The rapid geographic expansion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the infectious agent of Coronavirus Disease 2019 (COVID-19) pandemic, poses an immediate need for potent drugs that can help contain the outbreak. Enveloped viruses infect the host cell by cellular membrane fusion, a crucial mechanism required for virus replication. The SARS-CoV-2 spike glycoprotein, due to its primary interaction with the human angiotensin-converting enzyme 2 (ACE2) cell-surface receptor, is consid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…For the more recent SARS-CoV-2, imatinib’s viral inhibiting properties have been tested in vitro and results showed potential for inhibition, acting especially on the spike protein and blocking the viral entry at the endosomal level [ 69 ]. Prostaglandin E2 stimulation and the deceleration of the increase in TNF-α, IL1-β and IL-6 were observed in the case of administering imatinib, thus reducing inflammation.…”
Section: The Link Between Antiviral and Anticancer Drugsmentioning
confidence: 99%
“…For the more recent SARS-CoV-2, imatinib’s viral inhibiting properties have been tested in vitro and results showed potential for inhibition, acting especially on the spike protein and blocking the viral entry at the endosomal level [ 69 ]. Prostaglandin E2 stimulation and the deceleration of the increase in TNF-α, IL1-β and IL-6 were observed in the case of administering imatinib, thus reducing inflammation.…”
Section: The Link Between Antiviral and Anticancer Drugsmentioning
confidence: 99%
“…In another study, it improved with corticosteroids the respiration in SARS-CoV-2 pneumonia [34]. In addition, the Abl tyrosine kinase inhibitor (ATKI), imatinib was found to block viral fusion through attachment to receptorbinding domain (RBD) of SARS-CoV-2 spike protein [35]. In spite of all the previous treatment modalities, there is no proven curative agent for SARS-CoV-2 infection [36].…”
Section: Severe Acute Respiratory Syndrome Coronavirus-2 Sars-cov-2mentioning
confidence: 99%
“…Therefore, imatinib has been postulated to possibly have antiviral function against SARS-CoV-2. In fact, a recent study showed that imatinib binds to the receptor-binding domain (RBD) of SARS-CoV-2 spike protein and inhibits virus replication in vitro , indicating imatinib as a potential repurposed drug candidate for COVID-19 treatment ( 118 ). In a clinical case report, a patient with COVID-19 pneumonia displayed clinical improvement after receiving imatinib treatment, whereas the clinical condition deteriorated upon hydroxychloroquine (HCQ) and lopinavir/ritonavir (LPV/r) therapy ( 119 ).…”
Section: Repurposing Anticancer Medications For Covid-19 Treatmentmentioning
confidence: 99%